Termites in restoration: the forgotten insect?. Issue 8 (6th September 2021) - Wijas, Baptiste; Atkinson, Joe
Abstract : Few restoration studies consider soil invertebrates such as termites although these are present throughout many ecosystems worldwide and provide a range of ecosystem services as soil engineers. The few studies that do consider the recovery of termites after human‐induced disturbance are geographically concentrated in Africa and South America and tropical seasonal savannah ecosystems. These studies suggest that termites can in some cases recover to pre‐disturbance levels after a few years, or take up to 30 years, although with altered community composition. While termites could potentially have negative impacts on restoration efforts by damaging vegetation, their recovery was shown to have benefits on ecosystems which warrants further research into their recovery across a wider range of continents and biomes.